(untitled) (Khairulummah, 2023)
The text is a unique structural linguistic sound that adopts other text for its effectuation, the absorptive texts which are formulated from the linguistic profusions and eloquent expressions are imbricated in Ahmad Maqari’s poems for strengthening their words, enriching their meanings, affirming their conceptions, stabilizing their expressions. This article aims to study the significances of absorptive texts and the aesthetical style of the selected poems, the extent of which absorptive texts are interpenetrated with their influences in composing the poems together with their textual relationships by establishing linguistic mechanisms. It attends to analyse the sources of absorptive texts found in the poems, it discusses the functions of the absorptive texts, their linguistic and textual contents in the poems. it is designed to investigate the compatibility of absorptive texts in the poems. It employs the analytical and descriptive methods to investigate the components of absorptive words and meanings that are present in the selected poems in other to expose their potential delinquencies, significances and values. The article concludes that the absorptive texts are present in the poems and bestow them with perfected words, compatible meanings, excellent texts, proficient method, efficient formation, harmonized accuracy, symmetrical expressions and magnificent lyrics.